Humanity: Claremont Studies in the Philosophy of Religion, Conference 2019 - Dalferth, Ingolf U. (Religion in Philosophy and Theology, 2023)
Cover -- Title -- Preface -- Contents -- Ingolf U. Dalferth - Introduction: Humanity: An Endangered Idea? -- I. Philosophy -- Walter Schweidler - The Paradox of Humanity: Man's Self-Challenging Existence -- Daniel Chernilo - Humanism in Dark Times -- Raymond E. Perrier - The Logic of Humanism and the Ethics of Indeterminacy, Universalism, and Egalitarianism -- Lucas Wright - Broken Mirrors, Distorted Reflections: Anthropomorphism, the Recovery of the Concrétude of the Human in Rosenzweig, Heidegger, and Adorno and Horkheimer -- II. Theology -- Anselm K. Min - The Human Being as Image of God: Augustinian Meditations on the Contemporary Crisis of Humanity -- Petr Gallus - The Other Reduction? Capitalist Sensationalism and the Worldliness of God -- Veli-Matti Kärkkäinen - "Multidimensional Monism:" An Integrated and Diverse Embodied Theological Account of the imago Dei -- Ronald Cole-Turner - Transcendent Humanity: What if the Incarnation Really Matters? -- Daniel Nelson - Incarnate Humanity -- III. Transhumanism -- Hava Tirosh-Samuelson - Human Flourishing in the Age of Technology -- Thomas Jarred Farmer - Transhumanism, Religion, and the Anthropocene -- Jon Bialecki - Futures, Straining to Come into the World: Transhumanism, Transhumanisms, and the Moron Transhumanist Association -- Richard Livingston - On the Possibility of a Novel Phenomenon -- IV. Artificial Intelligence -- Dirk Evers - "Know Thyself " - Self-reflection and the Chances and Limits of Dataism -- Liu Yue - The Paradoxical Self: A Dilemma for Artificial General Intelligence -- Hasse Hamalainen - Conscience and Moral Cognition: What Distinguishes Us from Machines -- Nathan Schradle - Reframing Religion in the Algorithmic Age: Appraising the Algorithmic Approach to Religion -- Guelfo Carbone - Digital Technology and Embodiment: The Flesh as Paradigm -- V. Ethics.